Fabrication of ZnO incorporated chitosan nanocomposites for enhanced functional properties of cellulosic fabric. (3rd November 2016) - Raza, Z A; Anwar, F; Ahmad, S; Aslam, M
Abstract: This study concerns the fabrication of chitosan/zinc oxide nano-composites (CZNCs) by using a facile preparation method. The optical, structural and morphological features of nano-composites were investigated by using advanced analytical techniques. The developed CZNCs were coated on to woven cotton fabric by using the pad-dry-cure method. The coated fabric specimens were characterized for surface, functional and textile properties including antibacterial activity and (ultra violet) UV-blocking. The spectral and optical properties demonstrated that the nano-composites developed exhibited hexagonal structural pattern with an average particle size of about 50 nm. The resulting nano-composites were characterized by x-ray diffraction spectroscopy; scanning electron microscopy equipped with energy dispersive x-ray, dynamic light scattering technique and so forth. The incorporated concentration of zinc oxide nanoparticles affected both crystallite size and crystallinity of the nano-composites. The nano-composite coated cotton fabric exhibited durable antibacterial, UV-blocking and textile properties with a fair whiteness index.